Soft coral (Coelenterata octocoralia) composition and abundance in three intertidal areas in taklong Island National Marine Reserve, Nueva Valencia, Guimaras. - Exmundo, Howell Falco (1997.)
The study tries to identify up to the generic level the soft corals present in 3 areas within Taklong Island national Marine Reserve Guimaras. It also describes the distribution and abundance of these soft corals in the selected sites namely Piag-au I Piag-au II and Suruligan. The line intercept method was used to determine the living cover of soft corals and those of other life forms in the area. Gross morphological description and spicule analysis of each sample were made as basis for identification., Ten species belonging to 4 genera and two families were identified in the study area. There are 2 species of Sarcophyton, 3 species of Lobophytum, 4 species of Sinularia and 1 species of nephthea. Sarcophyton sp 1 was dominant species in 2 sites, Piag-au II, while Lobophytum sp 1 dominates in Suruligan. Factors (e.g. substratum type, water flow patters and wave action, and soft coral morphology and behavior) which may have accounted for the basic differences in the composition and distribution in the 3 study sites are discussed.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Corals -- Soft